Evaluation of potato (Solanum tuberosum) genotypes under heat stress condition (Current Horticulture, 2024)
Fifty-two potato (Solanum tuberosum L.) genotypes were evaluated in early crop season (75 days) at experimental field of ICAR-Central Potato Research Institute, Regional Station, Modipuram, Meerut, Uttar Pradesh, during 2020 and 2021. Significant differences were recorded among for tuber yield and tuber attributes like plant vigour (1-5 scale), foliage maturity (1-5 scale), tuber colour, tuber shape, eye depth and flash colour. The pooled results of 2020 and 2021 crop seasons indicated that eight genotypes namely Kufri Mohan (260 g), Kufri Lima (256 g), CP4149 (252g), Kufri Garima (241g), Kufri Bahar (239 g), CP3273 (236 g), Kufri Neelkanth (221 g), CP4143 (212 g), CP1326 (208 g) and Kufri Arun (207 g), were found high-yielding in term of total tuber yield/ plant. The highest marketable tuber yield/plant was recorded in Kufri Lima (234g), CP4149 (230 g), Kufri Mohan (225 g), CP3273 (213 g), Kufri Bahar (211 g), Kufri Garima (208 g), CP4143 (190 g), Kufri Neelkanth (182 g), Atlantic (178 g) and Kufri Arun (177 g). The genotypes, CP1931, CP3319, CP3322, CP3450, CP3470, CP3499, CP4149, CP4238, Kufri Garima, Kufri Lima, Kufri Surya and Lady Rossetta, were found highly tolerant with 0% hopper burn incidence. Most of the genotypes were highly tolerant with 0% mite damage incidence except CP3495, CP3341and CP3472 (20%) and Kufri Sindhuri and Kufri Pukhraj (40%). On an overall basis CP4149, Kufri Mohan, Kufri Garima and Kufri Lima were found promising for high plant stand, plant vigour, marketable/ total tuber yield, marketable/total tuber number and nil/low incidence of hopper and mite burn.
Keywords: Genotypes; Yield; Heat stress; Hopper and Mite burn